First Description of Sarcoptic Mange in a Free-Ranging European Wildcat (Felis silvestris silvestris) from Spain - Fernando Nájera; Elena Crespo; Amalia García-Talens; Rebeca Grande-Gómez; Francisco Javier Herrera-Sánchez; Michaela Gentil; Carmen Cortés-García; Elisabeth Müller; Rafael Calero-Bernal; Luis Revuelta (Animals, 2021)
Sarcoptic mange caused by the mite Sarcoptes scabiei is a worldwide-distributed skin infestation with a wide range of hosts, among them several species within the Felidae family. Sarcoptes scabiei was diagnosed in a dead adult female European wildcat (Felis silvestris silvestris) from Spain, based on histological evaluation of skin biopsies and identification of the arthropod from skin scrapings and molecular methods. This is the first description of Sarcoptes scabiei in a European wildcat. Due to its critical demography in the southernmost population of the Iberian Peninsula, the impacts of infectious diseases, including sarcoptic mange, as a new potential threat should be considered during disease surveillance programs of the species’ populations.